2019
DOI: 10.56093/ijas.v89i11.95357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and poultry manure on yield and nutrients uptake by maize (Zea mays)

Abstract: From this study we can conclude that significantly increase the yield of maize due to integrated nitrogen management could be further attributed to increased growth and vigour of plant as evident from increased growth attributes. So, the treatment combinations (T10) of 125 kg/ ha Nitrogen through inorganics plus 10 t/ha poultry manure through organics were having significant difference as compared to all other. This might be due to ready supply of nutrients through inorganic in the initial stages of crop growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
(3 reference statements)
3
9
0
Order By: Relevance
“…The results in table (8) showed that there are significant effects between chemical fertilizer levels compared with control on yield g plant⁻¹, the highest value was from 50% of recommended chemical fertilizer application(84.99 g) where's the lowest was from control (72.50 g ) with the rate of increase 17%, also in type and levels of organic The interaction between chemical fertilizer levels, types and levels of organic fertilizers affected significantly (p ≤ 0.05) on yield (g plant -1) , the highest value (104.5 g) obtained from interaction ( 50% of recommended chemical fertilizer and 4 ton ha -1 of domestic organic fertilizer ) and the lowest value (49.1 g) obtained from control of chemical and two types of organic fertilizers, with the rate of increase 112.8% These results agree with [34] on maize plants that they found an increase of yield by increasing of nitrogen and poultry manure levels. *P.M.=poultry manure.…”
Section: Yield Per Plant (G)supporting
confidence: 83%
“…The results in table (8) showed that there are significant effects between chemical fertilizer levels compared with control on yield g plant⁻¹, the highest value was from 50% of recommended chemical fertilizer application(84.99 g) where's the lowest was from control (72.50 g ) with the rate of increase 17%, also in type and levels of organic The interaction between chemical fertilizer levels, types and levels of organic fertilizers affected significantly (p ≤ 0.05) on yield (g plant -1) , the highest value (104.5 g) obtained from interaction ( 50% of recommended chemical fertilizer and 4 ton ha -1 of domestic organic fertilizer ) and the lowest value (49.1 g) obtained from control of chemical and two types of organic fertilizers, with the rate of increase 112.8% These results agree with [34] on maize plants that they found an increase of yield by increasing of nitrogen and poultry manure levels. *P.M.=poultry manure.…”
Section: Yield Per Plant (G)supporting
confidence: 83%
“…And Nitrogen is essential for the growth and development of maize plants. It is an important component of chlorophyll, the pigment responsible for photosynthesis, and amino acids, which are the building blocks of proteins [38]. The result obtain is in line with [25], where sugarcane waste straw biochar, in comparison with Farm Yard Manure and NPK, significantly improved okra plant growth and yield parameters over the control, FYM and NPK.…”
Section: Plant Growth and Developmentsupporting
confidence: 57%
“…There was no much difference between maize D and Maize E, although no sign of grain was observed in maize E as it still looks to be developing at that moment but the cob was a bit bigger and taller to that of maize D, this is probably due to the slow release of the nutrient present in the rabbit manure and insufficient nitrogen and phosphorous, as adequate nitrogen supply is essential for optimum maize growth and yield potential. According to a study by [38], nitrogen application significantly increased the grain yield and biomass production of maize plants while phosphorus is important for root development, seedling growth, and flowering [40]. Maize B despite being the tallest plant among all, have an average yield when compared to maize A and maize C, it maturity was fast compared to the two, this is clearly due to the imbalance of nutrient mostly inadequacy in nitrogen because potassium is important for the development of strong stems and roots and maize cobs [41].…”
Section: Yield Of Maize a B C D And Ementioning
confidence: 99%
See 1 more Smart Citation
“…This crop is commonly cultivated for it is highly proteinated edible seeds, although it can also be produced as fodder. 3 Chickpea crop is prone to biotic factors, which leads to its low yield. 4 Numerous viral, bacterial, fungal, and nematode diseases can infect chickpea pulse crop.…”
Section: Introductionmentioning
confidence: 99%